IMPLEMENTASI PENDEKATAN PEMBELAJARAN MENDALAM DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Taufiqur Rochman, Mohammad; Iswatiningsih, Daroe; Deny Damara, Tio (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the deep learning approach in Indonesian language learning at the elementary school level. The study is motivated by the fact that conventional teacher-centered learning methods are still dominant, causing students to be less active, less critical, and easily bored during the learning process. The deep learning approach was chosen because it encourages students to understand learning materials more meaningfully through the application of mindful learning, meaningful learning, and joyful learning. This study employed a qualitative approach with a descriptive research design. The research subjects consisted of elementary school teachers and students involved in Indonesian language learning. Data collection techniques included observation, interviews, and documentation. The data were analyzed using an interactive analysis model consisting of data reduction, data presentation, and conclusion drawing. The findings revealed that the implementation of the deep learning approach was able to create a more active, interactive, and meaningful learning process. The application of mindful learning helped students become more focused and aware during the learning process. Meaningful learning enabled students to understand the material by connecting it to their daily life experiences, while joyful learning created an enjoyable classroom atmosphere and increased students’ learning motivation. In addition, the deep learning approach also improved students’ language skills, including listening, speaking, reading, and writing, as well as enhancing critical thinking, creativity, communication, and collaboration skills. Therefore, the deep learning approach is considered relevant for implementation in Indonesian language learning at the elementary school level because it can improve the quality of learning and support the development of students’ 21st-century skills.